Inter- and intra-rater reliability of carpal tunnel volume measurement. Issue 2 (4th March 2022) - Anderson, Drew A.; Miller, Mackenzie J.; Agur, Anne M.; Oliver, Michele L.; Gordon, Karen D.
ABSTRACT: The reliability of carpal tunnel volume (CTV) measurement has not been previously reported. This study evaluated inter- and intra-rater reliability and assessed the variability of image segmentation and anatomical landmark selection. Analysis was performed by two raters on computed tomography images collected on two cadaveric specimens in neutral wrist posture. The variability of landmark selections was less than 0.3 mm. Intra-class correlation coefficients (ICC) for segmentation surpassed 0.88. The carpal tunnel volume calculations had ICC values greater than 0.98. These results suggest carpal tunnel volume can be reliably measured using the methods outlined in this study.